Penggunaan Media Audio Visual Untuk Meningkatkan Motivasii Siswa Pada Pembelajaran PAI di SMK Negeri 2 Painan - Diana Livia (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study aims to enhance students' motivation and understanding in Islamic Religious Education (PAI) learning through the use of audio-visual media at SMK Negeri 2 Painan. This Classroom Action Research (CAR) was conducted in three cycles, including planning, action implementation, observation, and reflection. The findings revealed that the use of audio-visual media significantly increased student motivation from 65% in the first cycle to 90% in the third cycle. Students' understanding of the material also improved with the use of more dynamic and interactive media. The success factors included the alignment of media with students' needs, adequate technological facilities, and teachers' skills in utilizing audio-visual media. Despite challenges such as limited technological access and less optimal media duration, the results indicate that audio-visual media effectively enhance student engagement and learning outcomes.